Determination by GC-IT/MS of Phytosterols in Herbal Medicinal Products for the Treatment of Lower Urinary Tract Symptoms and Food Products Marketed in Europe - Müller, Christoph; Bracher, Franz (Planta Medica, 2015)
A method for the determination of phytosterols in herbal medicinal products for the treatment of lower urinary tract symptoms and food products is described here. Using a convenient sample preparation protocol and sensitive gas chromatography ion trap mass spectrometry analysis, ten different sterols, among them five Δ7-phytosterols as typical constituents of pumpkin seed preparations, could be identified and quantified. This protocol was applied to the analysis of 31 marketed products, from which seven were raw materials.
Keywords: gas chromatography ion trap mass spectrometry; Δ7-phytosterols; pumpkin seed extracts; saw palmetto extracts; lower urinary tract symptoms (LUTS)